Factors affecting quality of life on communities in Selangor - Mohamed Osman, Mariana; Rosli, Nur Farhanah; Rabe, Noor Suzilawati; Jaafar, Samsuddin (American Scientific Publishers, 2018)
The concept of quality of life is much wider than the standard of living material living condition. It correspondingly includes working condition, the degree of social integration, health and education whether people are particularly fragile economically or not (Albouy et al., 2010). But, the effects of quality of life in every places or city may vary in their life pattern. The notion of having an excellent quality of life has a much different understanding as Mohit (2013) also granted that diverse regions of the world have defined the quality of life differently. This paper highlights the factors affecting the quality of life by the communities in one of the states in Malaysia namely Selangor. In another word, the major contributor of their life to be more quality will be assessing. Hence, one of the research question for the paper is related to the current level of quality of life among the communities in Selangor. The research objectives are to identify the major contributor towards the level of quality of life in Selangor and to identify the significant between the quality of life of communities in Selangor and the elements of quality of life. The expected outcome of this paper is to know, which of the several elements in the quality of life, does affect the quality of life for the residents in Selangor.